Uncovering subclinical diseases in sacrificial livestock in Kulon Progo, Indonesia: A comparative approach using ante-mortem and post-mortem inspections - Awaludin, Aan; Nugraheni, Yudhi Ratna; Arnuphapprasert, Apinya; Wibowo, Sarwo Edy; Widiarso, Budi Purwo; Prastowo, Joko; Nurcahyo, Raden Wisnu; Andityas, Morsid; Muhamad, Nur; Nurfitriani, Rizki Amalia (Politeknik Negeri Jember, 2026)
Some cases of animal diseases are difficult to detect clinically, especially chronic and subclinical diseases. The condition of subclinical diseases poses the potential for hidden disease spread within a livestock population. This research aims to uncover subclinical diseases occurring in sacrificial livestock. The methodology employed involved a combination of ante-mortem and post-mortem examinations performed on the same individual animals. The study was conducted in Bunder Tengah, located within the Progo River watershed area. The subjects of the study consisted of four male cattle, eight male Etawa Crossbred goats (ECG), and one ram. The results indicated that during the ante-mortem examination, all animals were diagnosed as clinically healthy; however, the post-mortem examination revealed that two cattle (ID: BC-1 and BC-4) and one goat (ID: G-4) were infected with fasciolosis. The conclusion of this study is the combination of ante-mortem and post-mortem inspections can be used to uncover clinically hidden diseases, allowing information about disease occurrences in a region to be continuously monitored and identified, which can then serve as a guideline in planning disease prevention programs. Laboratory examinations as part of ante-mortem inspections should be conducted to obtain early information about disease occurrences in a particular area.